2017
DOI: 10.1002/ana.25026
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine transporter imaging deficit predicts early transition to synucleinopathy in idiopathic rapid eye movement sleep behavior disorder

Abstract: DAT-SPECT identifies IRBD patients at short-term risk for synucleinopathy. Decreased FP-CIT putamen uptake greater than 25% predicts synucleinopathy after 3 years' follow-up. These observations may be useful to select candidates for disease modification trials in IRBD. Ann Neurol 2017;82:419-428.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
124
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(134 citation statements)
references
References 37 publications
9
124
0
1
Order By: Relevance
“…However, up to 45% of patients showed, in concomitance, the presence of a symptom that has been linked to a higher PD risk, pointing out to the possibility that a subtle neuronal degeneration is taking place. Unfortunately, no risk factor able to predict prospectively the conversion from RBD to a neurodegenerative disease can be indicated ( 27 ), the only tool that has demonstrated reliable predictive value being 123 I-FP-DAT-SPECT ( 28 ). In this light, we believe that the consistent finding of VEMPs dysfunction in our cohort is potentially relevant in the context of the search of biomarkers for neurodegeneration in patients displaying prodromal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, up to 45% of patients showed, in concomitance, the presence of a symptom that has been linked to a higher PD risk, pointing out to the possibility that a subtle neuronal degeneration is taking place. Unfortunately, no risk factor able to predict prospectively the conversion from RBD to a neurodegenerative disease can be indicated ( 27 ), the only tool that has demonstrated reliable predictive value being 123 I-FP-DAT-SPECT ( 28 ). In this light, we believe that the consistent finding of VEMPs dysfunction in our cohort is potentially relevant in the context of the search of biomarkers for neurodegeneration in patients displaying prodromal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…9 Another study in subjects with polysomnogram-confirmed RBD without a diagnosis of PD found that >50% of cases had evidence of a subclinical DAT deficit, and that these patients were more likely to develop PD or DLB over 4 years of follow-up. 11,13 A multicenter investigation of risk of neurodegeneration in RBD also found a high rate of conversion to either PD or DLB. 14 We did not observe a high rate of transition to a dementia phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Some of these changes have been observed in cohorts with genetic risk factors for PD, 9,10 or in cohorts with rapid eye movement sleep behavior disorder (RBD). [11][12][13][14] However, the prodromal stage for sporadic PD has been less extensively studied.…”
Section: ---------------------------------------------------------mentioning
confidence: 99%
“…Whereas the conversion rate to synucleinopathy in clonazepam-treated RBD patients is high [2, 3, 6], no comparable data are available yet for melatonin-treated RBD patients. Our observation warrants further documentation of positive melatonin effects on conversion rate in RBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In patients suspected to suffer from a beginning synucleinopathy, DA transporter density scintigraphy (DaTSCAN) is the diagnostic tool of choice to prove pathology [5]. Moreover, a DA transporter imaging deficit predicts early transition to synucleinopathy in RBD patients [6]. …”
Section: Introductionmentioning
confidence: 99%